Associations between methadone maintenance treatment and crime: a 17‐year longitudinal cohort study of Canadian provincial offenders. (19th November 2017) - Russolillo, Angela; Moniruzzaman, Akm; McCandless, Lawrence C.; Patterson, Michelle; Somers, Julian M.
Abstract: Aims: To estimate and test the difference in rates of violent and non‐violent crime during medicated and non‐medicated methadone treatment episodes. Design, Setting and Participants: The study involved linkage of population level administrative data (health and justice) for all individuals ( n = 14 530) in British Columbia, Canada with a history of conviction and who filled a methadone prescription between 1 January 1998 and 31 March 2015. Methadone maintenance treatment was the primary independent variable and was treated as a time‐varying exposure. Each participant's follow‐up (mean: 8 years) was divided into medicated (methadone was dispensed) and non‐medicated (methadone was not dispensed) periods with mean durations of 3.3 and 4.6 years, respectively. Measurements: Socio‐demographics of participants were examined along with the main outcomes of violent and non‐violent offences. Findings: During the first 2 years of treatment (≤ 2.0 years), periods in which methadone was dispensed were associated with a 33% lower rate of violent crime [0.67 adjusted hazard ratio (AHR), 95% confidence intervals (CI) = 0.59, 0.76] and a 35% lower rate of non‐violent crime (0.65 AHR, 95% CI = 0.62, 0.69) compared with non‐medicated periods. This equates to a risk difference of 3.6 (95% CI = 2.6, 4.4) and 37.2 (95% CI = 33.0, 40.4) fewer violent and non‐violent offences per 100 person‐years, respectively. Significant but smaller protective effects of dispensed methadone were observed across longer treatment intervals (2.0 to ≤ 5.0 years, 5.0 to ≤ 10.0 years). Conclusions: Among a cohort of Canadian offenders, rates of violent and non‐violent offending were lower during periods when individuals were dispensed methadone compared with periods in which they were not dispensed methadone.